Determination of anthropogenic and biogenic compounds on atmospheric aerosol collected in urban, biomass burning and forest areas in São Paulo, Brazil - Vasconcellos, P. (2010)
This study was conducted at three sites of different characteristics in São Paulo State: São Paulo (SPA), Piracicaba (PRB) and Mata Atlântica Forest (MAT). PM10, n-alkanes, pristane and phytane, PAHs, water-soluble ions and biomass burning tracers like levoglucosan and retene, were determined in quartz fiber filters. Samplings occurred on May 8th to August 8th, 2007 at the MAT site; on August 15th to 29th in 2007 and November 10th to 29th in 2008 at the PRB site and, March 13th to April 4th in 2007 and August 7th to 29th in 2008 at the SPA site.Aliphatic compounds emitted biogenically were less abundant at the urban sites than at the forest site, and its distribution showed the influence of tropical vascular plants. Air mass transport from biomass burning regions is likely to impact the sites with specific molecular markers.The concentrations of all species were variable and dependent of seasonal changes. In the most dry and polluted seasons, n-alkane and cation total concentrations were similar between the megacity and the biomass burning site. PAHs and inorganic ion abundances were higher at São Paulo than Piracicaba, yet, the site influenced by biomass burning seems to be the most impacted by the organic anion abundance in the atmosphere. Pristane and phytane confirm the contamination by petroleum residues at urban sites; at the MAT site, biological activity and long range transport of pollutants might influence the levels of pristane.